2018
DOI: 10.1002/cpps.53
|View full text |Cite
|
Sign up to set email alerts
|

Solubilization, Folding, and Purification of a Recombinant Peptidoglycan‐Associated Lipoprotein (PAL) Expressed in Escherichia coli

Abstract: Studies aiming at heterologous expression of highly hydrophobic proteins, such as outer membrane proteins in general and peptidoglycan-associated lipoprotein (PAL) in particular, are not trivial due to difficulties in obtaining recombinant protein in a soluble state, which is desired because it allows purification by traditional chromatographic methods. PAL is associated with the integrity of the cellular envelope in Gram-negative bacteria and interacts strongly with the peptidoglycan layer. However, it is inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
(24 reference statements)
1
5
0
Order By: Relevance
“…In the fifth group, peptidoglycan-associated proteins, including (I) Peptidoglycan-associated lipoprotein Pal (WP_058148283.1) and (II) Glycosyl hydrolase family 18 protein (WP_034004678.1), are among the shortlisted immunogenic targets against P. aeruginosa. In Gram-negative bacteria, Pal is related to the integrity of the cellular envelope and interacts powerfully with the peptidoglycan layer [75]. Consistent with our results, it was recently…”
Section: Plos Onesupporting
confidence: 91%
“…In the fifth group, peptidoglycan-associated proteins, including (I) Peptidoglycan-associated lipoprotein Pal (WP_058148283.1) and (II) Glycosyl hydrolase family 18 protein (WP_034004678.1), are among the shortlisted immunogenic targets against P. aeruginosa. In Gram-negative bacteria, Pal is related to the integrity of the cellular envelope and interacts powerfully with the peptidoglycan layer [75]. Consistent with our results, it was recently…”
Section: Plos Onesupporting
confidence: 91%
“…This domain targets several l -arabinose bonds present in hemicellulose, as does AbfB 24 , 26 . For the purification of ThABF, it was necessary to use a refolding method adapted to recover the protein from inclusion bodies in its best oligomeric state 28 . The final protein yield following purification was relatively low, at 0.51 mg/mL, which made it difficult to carry out other types of biochemical tests; however, the method allowed us to characterize the enzyme and study it, as demonstrated in other studies 28 , 29 .…”
Section: Discussionmentioning
confidence: 99%
“…After rupturing the cells and resuspending the inclusion bodies, the refolding protocol of Santos et al 28 was applied. The pellet was resuspended in 15 mL of buffer A containing 1 M urea.…”
Section: Methodsmentioning
confidence: 99%
“…This domain targets several L-arabinose bonds present in hemicellulose, as does AbfB 24,26 . For the purification of ThABF, it was necessary to use a refolding method adapted to recover the protein from inclusion bodies in its best oligomeric state 28 . The final protein yield following purification was relatively low, at 0.51 mg/ml, which made it difficult to carry out other types of biochemical tests; however, the method allowed us to characterize the enzyme and study it, as demonstrated in other studies 28,29 . In the tests with different substrates, we demonstrated that ThABF exerted activity on the substrates pNPG, pNPAp, pNPF and pNPAra.…”
Section: Discussionmentioning
confidence: 99%
“…The ThABF gene was cloned into the pET-28a (+)vector using the standard gene cloning protocol of Sambrook 43 After rupturing the cells and resuspending the inclusion bodies, the refolding protocol of Santos et al 28 was applied. The pellet was resuspended in 15 mL of buffer A containing 1 M urea.…”
Section: Heterologous Production and Refolding Of Tibgal54amentioning
confidence: 99%